Application of Density Functional Approximation for Investigation of Reactive Sites, Molecular and Electronic Structure of Coumarins and Their Lanthanide(III) Complexes - Trendafilova, Natasha; Kostova, Irena (Asian Journal of Chemistry, 2012)
DFT approximation was applied for investigation of a series di-[4-hydroxycoumain]s. Different basis sets were tested in the course of the calculations. The calculated hydrogen bond energies revealed two equivalent hydrogen bonds in DC and two different in strengths hydrogen bonds in PhDC and PyDC. Further, the effect of the substutient on the hydrogen bond asymmetry and the electron density distribution was evaluated. Molecular quantities as vertical ionization potential, electron affinity, electronegativity, hardness and electrophilicity indices of the neutral species, were calculated and discussed at the optimized geometries. Molecular electrostatic potential was applied for predicting the most probable sites for electrophilic attack. Since the active forms of the compounds studied are their ionic species, next, the molecular and electronic structures as well as the reactive sites of the dianionic species were studied. The theoretical results suggested that both carbonyl and both hydroxyl oxygen atoms are preferred binding sites for electrophilic attack for a metal coordination.